V. V. Sapozhnikov and Questions of Spiritual Education in Siberia in 1918—1919 - I. V. Petrov (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
A little-known fact in the history of churchstate relations on the territory of Siberia is considered: the reforms that affected theological schools and public education in 1918—1919. The relevance of the study is due to the unresolved problems of teaching religious subjects in modern Russia. The author’s attention is focused on the figure of Vasily Vasilyevich Sapozhnikov, an outstanding researcher and geographer, traveler who during the Civil War held the post of Minister of Public Education in the anti-Bolshevik governments. The most important event is covered — the Siberian Council Meeting of 1918, which was a continuation of the Local Council of 1917—1918 at the local level. It is shown that it was at the end of 1918 in Tomsk that representatives of non-Bolshevik political parties, public figures and clergy tried to resolve the long-awaited issue of changes in the structure of spiritual education in Russia, as well as in the reform of teaching the Law of God in Russia. The novelty of the study lies in the fact that it managed to combine the literature about Vasily Sapozhnikov published over the past decades with the recently published documents on the Siberian Council Meeting.